Development of Metamodels as Logical and Algebraic Systems - Mezhuyev, Vitaliy (2014)
The new approach to development of metamodels for domain specific modelling is proposed in the paper. The logical system for expressing domain specific knowledge is linked with an algebraic structure, defined at the meta-metamodel level. This allows to take into account the mathematical structure of modelled domains, and to use algebraic operations for development of new effective methods for solving domain specific tasks. The applicability of the approach for development of the metamodel “Vector Logic” is shown. Vector logic is a diagrammatic system of propositional logic in which propositions are vectors in the logical space. Practical implementation of the metamodel in the Vector Logic Visual 3D Environment is considered.